Genetics of Cardiovascular Disease: Fishing for Causality - Paone, Christoph; Diofano, Federica; Park, Deung-Dae; Rottbauer, Wolfgang; Just, Steffen (Frontiers in Cardiovascular Medicine, 2018)
Cardiovascular disease (CVD) is still the leading cause of death in all western world countries and genetic predisposition in combination with traditional risk factors frequently mediates their manifestation. Genome-wide association (GWA) studies revealed numerous potentially disease modifying genetic loci often including several SNPs and associated genes. However, pure genetic association does not prove direct or indirect relevance of the modifier region on pathogenesis, nor does it define within the associated region the exact genetic driver of the disease. Therefore, the relevance of the identified genetic disease associations needs to be confirmed either in monogenic traits or in experimental in vivo model system by functional genomic studies. In this review, we focus on the use of functional genomic approaches such as gene knock-down or CRISPR/Cas9-mediated genome editing in the zebrafish model to validate disease-associated genomic loci and to identify novel cardiovascular disease genes. We summarize the benefits of the zebrafish for cardiovascular research and highlight examples demonstrating the successful combination of GWA studies and functional genomics in zebrafish to broaden our knowledge on the genetic and molecular underpinnings of cardiovascular diseases.